Os recebimentos de relíquias em S. Roque (Lisboa 1588) e em Santa Cruz (Coimbra 1595) : relíquias e espiritualidade : e alguma ideologia - Carvalho, José Adriano de Freitas (2001)
Preliminary study of some cases of relics translated during the second half of the 16th century in Portugal: the relics donated by D. Juan de Borja (ambassador of Phillip II to Portugal and Germany, mordomo-mor at the Court of Empress Mary of Austria, etc.) to the Church of S. Roque in Lisbon (1588) and the relics donated by D. Félix de Rojas (a canon regular) to the Monastery of Santa Cruz of Coimbra in 1595. The study of that period detailed accounts not only throws some light in very important aspects of the spirituality conveyed by the sermons and celebrations held during those ceremonies, but also allow us to understand some of the social and political aspects observed in Portugal in the early days of a dynastic peninsular union.